2006
DOI: 10.1007/s11881-006-0003-5
|View full text |Cite
|
Sign up to set email alerts
|

Reading fluency: The whole is more than the parts

Abstract: This study examined the relative contributions of phonological awareness, orthographic pattern recognition, and rapid letter naming to fluent word and connected-text reading within a dyslexic sample of 123 children in second and third grades. Participants were assessed on a variety of fluency measures and reading subskills. Correlations and hierarchical multiple regression analyses were carried out to explore these relationships. The results demonstrate that phonological awareness, rapid letter naming, and ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
80
1
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(102 citation statements)
references
References 47 publications
13
80
1
8
Order By: Relevance
“…Methods: Seven individuals who have undergone left cerebral hemispherectomy to control intractable seizures associated with perinatal infarct have been recruited for this study. We examined if components of phonological processing that are shown to reliably separate average readers from struggling readers, i.e., phonological awareness, verbal memory, speed of retrieval, and size of vocabulary, show the same relationship to reading levels when they are mediated by the right hemisphere [2]. Results: We found that about 60% of our group developed both word reading and paragraph reading in the average range.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Methods: Seven individuals who have undergone left cerebral hemispherectomy to control intractable seizures associated with perinatal infarct have been recruited for this study. We examined if components of phonological processing that are shown to reliably separate average readers from struggling readers, i.e., phonological awareness, verbal memory, speed of retrieval, and size of vocabulary, show the same relationship to reading levels when they are mediated by the right hemisphere [2]. Results: We found that about 60% of our group developed both word reading and paragraph reading in the average range.…”
mentioning
confidence: 88%
“…1 The PM part assesses the size of short-term verbal storage and included memory for digits and nonword repetition. 2 The RN portion estimates the ability to quickly retrieve phonological forms (names) associated with graphic stimuli and included naming digits and letters. 3 …”
Section: Phonological Processing Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Because reading fulfills many purposes such as personal, social, socio-civic, avocational, professional, Lovett, 2006;Francis, Fletcher, Stuebing, Lyon, Shaywitz & Shaywitz, 2005). Oral fluency is frequently described in different studies as having three major dimensions such as word reading accuracy; automaticity or word reading rate or pace and prosody (Rasinski, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…interventions are being developed and tested that focus on dual aspects of reading difficulties: speed and decoding (Katzir et al, 2006;Wolf, Miller, & Donnelly, 2000).…”
Section: Word Reading In the Current Sample Of Survivorsmentioning
confidence: 99%